Local pointwise second derivative estimates for strong solutions to the σk-Yamabe equation on Euclidean domains - Duncan, JAJ; Nguyen, LUC (Springer Nature, 2021)
We prove local pointwise second derivative estimates for positive W2,p solutions to the σk-Yamabe equation on Euclidean domains, addressing both the positive and negative cases. Generalisations for augmented Hessian equations are also considered.